Similarities and differences in international clinical practice guidelines for preeclampsia diagnosis and diagnostics: a scoping review - Mónica Chamillard; Virginia Díaz; Celina Gialdini; Julia Pasquale; Anayda Portela; Edgardo Abalos (Hypertension in Pregnancy)
Introduction Preeclampsia is a leading cause of maternal and newborn deaths. Traditionally characterized by high-blood pressure and proteinuria, organ and placental dysfunction were later proposed in some clinical practice guidelines as additional components for its definition. Variability in diagnostic criteria across international guidelines could be a barrier to harmonized and equitable care in different settings.Methods We reviewed current relevant clinical practice guidelines to identify similarities and differences in recommendations related to the definition and diagnosis of preeclampsia, and their supporting evidence. We also reviewed additional systematic reviews related to the diagnosis of preeclampsia. We searched different databases and websites of international and professional organizations for guidelines published or updated from 2014 to 2024. We searched databases to identify additional systematic reviews on preeclampsia diagnosis.Results Fifteen guidelines from 11 organizations were identified with 11 systematic reviews supporting evidence on the diagnosis of preeclampsia. We found 21 additional systematic reviews, not included in these guidelines.Discusion There is agreement for hypertension and proteinuria for the diagnosis of preeclampsia, without a uniform consensus on methods and devices for their assessment. Organ dysfunction is considered in eight guidelines and placental dysfunction in four, with some disagreements on their usefulness, and the methods and tools for their measurement. Few guidelines support their recommendations on preeclampsia diagnosis with systematic reviews.Conclusion Consensus in preeclampsia definition is needed to guide not only clinical practice but also future research and policy, particularly in global health contexts.